THE USE OF PICTURE CARD MEDIA TO IMPROVE 12TH GRADE STUDENTS’ MASTERY OF GERMAN VOCABULARY - Junita G. Belangkaehe; Soflies M. E. Bingku; Prilimercy E. Kojongian (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
The present study aims at describing the use of picture card media to improve 12th grade students’ mastery of German vocabulary. This Classroom Action Research (CAR) is conducted at SMA Negeri 1 Tamako in June to August 2023. The methods used to collect research data are class observations, interviews and tests. This action research uses a qualitative descriptive data analysis methodology which is carried out in two cycles, each cycle includes planning, implementing actions, observing and reflecting. The findings show that the use of picture card media can improve 12th grade students’ mastery of German vocabulary. The increase in student activity can be seen from the average pre-action activity score of 34.61%, cycle I was 3.33% and cycle II was 3.11% of the maximum score. The percentage increase in student activity from pre-action to cycle I was 47.66%, then the percentage increase again from cycle I to cycle II was 7.88%. So the average increase in student activity scores was 9.68%.